An Analysis of the Students’ Gestures in Speaking Class at Mahadikarya Courses - Septiberliana Musdalifah (Journal of Teaching and Education, 2022)
The research questions of this research were 1) what kinds of gestures thatused by the students in speaking class?, 2) what were the functions ofsuch kinds of gestures used by the students in speaking class ?, 3) what were the students’ perception toward using gestures when speaking?. The objective of the research was to find out several kinds of gestures used by the students when speaking, find out function of gestures used by the students, and to find out the students’ perception toward using gesture when speaking. The design of this research was descriptive qualitative method. The instruments that were used in this research were questionnaire, observation and interview guideline. Participants of this research were 10 students in Intermediate class at Mahadikarya Courses.  The researcher found that there were 12 kinds of gesture used by the students when speaking. The function of gesture used by the students was also various It was as a symbol money, to visualize the number and enhace verbal message, to show emphasis what’s being said, to indicate self, to help conveyed the words, to help express idea, show felt ashamed, show the person forget, show a message “ok”, show disagreement, show a positive message, Show the person is politely. And the students perception toward used gesture when speak also varied. Most said that gesture to make the speakers more self-confidence, comfortable, and relax convey idea.